Antimicrobial Resistance Profile of Common Foodborne Pathogens Recovered from Livestock and Poultry in Bangladesh - Kazi Rafiq; Md Rafiqul Islam; Nure Alam Siddiky; Mohammed Abdus Samad; Sharmin Chowdhury; K. M. Mozaffor Hossain; Farzana Islam Rume; Md Khaled Hossain; ATM Mahbub-; Md Zulfekar Ali; Moizur Rahman; Mohammad Rohul Amin; et al. (MDPI AG, 2022)
Multidrug-resistant (MDR) foodborne pathogens have created a great challenge to the supply and consumption of safe & healthy animal-source foods. The study was conducted to identify the common foodborne pathogens from animal-source foods & by-products with their antimicrobial drug susceptibility and resistance gene profile. The common foodborne pathogens Escherichia coli (E. coli), Salmonella, Streptococcus, Staphylococcus, and Campylobacter species were identified in livestock and poultry food products. The prevalence of foodborne pathogens was found higher in poultry food & by-product compared with livestock (p < 0.05). The antimicrobial drug susceptibility results revealed decreased susceptibility to penicillin, ampicillin, amoxicillin, levofloxacin, ciprofloxacin, tetracycline, neomycin, streptomycin, and sulfamethoxazole-trimethoprim whilst gentamicin was found comparatively more sensitive. Regardless of sources, the overall MDR pattern of E. coli, Salmonella, Staphylococcus, and Streptococcus were found to be 88.33%, 75%, 95%, and 100%, respectively. The genotypic resistance showed a prevalence of blaTEM, blaSHV, blaCMY, tetA, tetB, sul1, aadA1, aac(3)-IV, and ereA resistance genes. The phenotype and genotype resistance patterns of isolated pathogens from livestock and poultry had harmony and good concordance, and sul1 & tetA resistance genes had a higher prevalence. Good agricultural practices along with proper biosecurity may reduce the rampant use of antimicrobial drugs. In addition, proper handling, processing, storage, and transportation of foods may decline the spread of MDR foodborne pathogens in the food chain.